1993
DOI: 10.1007/bf00032964
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in peanut: Influence of growth regulators and sugars

Abstract: A b s t r a c tSomatic embryogenesis and plant regeneration were induced from immature embryonal axes and immature cotyledons of peanut (Arachis hypogaea L. fastigata type cv JLM-1). Influence of different auxins, cytokinins and sugars on somatic embryogenesis from immature cotyledon explants was also investigated. Among the different auxins tested, 2,4-dichlorophenoxyacetic acid (2,4-D) was most effective, producing the highest frequency of responding cultures and highest average number of somatic embryos per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…These plants were transferred to pots (Figure 1c-e), with an ex vitro survival rate of 80%, where they grew normally and produced seeds. Our results coincide with those that reported the effectiveness of PIC on the induction of somatic embryos of A. hypogaea (Sellars et al, 1990;Eapen and George, 1993;Little et al, 2000), A. pintoi (Rey et al, 2000), A. glabrata (Vidoz et al, 2004) and A. paraguariensis (Sellars et al, 1990).…”
supporting
confidence: 95%
“…These plants were transferred to pots (Figure 1c-e), with an ex vitro survival rate of 80%, where they grew normally and produced seeds. Our results coincide with those that reported the effectiveness of PIC on the induction of somatic embryos of A. hypogaea (Sellars et al, 1990;Eapen and George, 1993;Little et al, 2000), A. pintoi (Rey et al, 2000), A. glabrata (Vidoz et al, 2004) and A. paraguariensis (Sellars et al, 1990).…”
supporting
confidence: 95%
“…The reason was that the combination of 2,4-D and cytokinines led to the development of non-embryogénie callus. The inhibitory effect of cytokinins on somatic embryogenesis was also reported in species like Arachis hypogaea (Eapen & George 1993), Pisum sativum (Loiseau et al 1995), and Dendranthema grandiflorum (Tanaka et al 2000). The obtained result indicated that the induction of embryogénie callus was the most optimum on the MS medium containing 2-5piM 2,4-D alone.…”
supporting
confidence: 57%
“…The use of cytokinins has generally given conflicting results; although zeatin and 2,4-D enhanced somatic embryogenesis in Arachis hypogaea, the addition of other cytokinins (benzylaminopurine or kinetin) decreased the embryogenic response (Eapen and George 1993). Initially callus was green but later it turned brown.…”
mentioning
confidence: 98%